Taṭbīq Uslūb al-Munāẓarah ‘ala Tarqiyyah Mahārah al-Kalām (Dirāsah Ijrā’iyyah laday al-Ṭullāb fī al-Sanah al-Sādisah bi Ma’had ‘Ulūm al-Dīn Lhokseumawe) - Zurriyati Zurriyati (DAYAH: Journal of Islamic Education, 2020)
The Ma’had Ulumuddin Lhokseumawe is one of the institutes that encourages students to speak in Arabic. They must use it every day for avoidance and fear of punishment. Students try to use Arabic as much as they know, although there are mistakes. Based on these phenomena support the researcher to correct them. The purposes of this study are identify and analyze the common mistakes of female student, as well as identify the main reasons behind this phenomenon.The method used by the researcher is descriptive analytical study, where described these studies for the existence of mistakes in speech by students at the Ma’had Ulumuddin. The research community is all the 500 students of junior-level. The researcher took 10% of the sampel, that is 50 students of first level. Sampling method is porposive sampling.The results showed that: (1) The common mistakes that occur between students during the communication between them of the kafaiyyah mistakes. That's at 77 or 84.61%. And the adaiyyah mistakes revolve between them less than the limit, which is on the amount of 14 or 15.39%. (2) Student error analysis is divided into four (a) grammatical errors for 38.88%, which are most of the errors that occurred. Followed by (b) semantic errors for 35,55%, and (c) capital errors of 18.88%. And (d) technological errors for 6.69%. Which are the low mistakes that occurred between them.(3) Two main causes of the causes of this phenomenon, which are the errors are: (a) The reasons related to students, the weakness of the Arabic language, and this indicates that the structure or sentence that the students brought confused the language of the mother, Match between the verb and the actor in terms of recall, femininity and others. And (b) the reasons related to the teacher thereof, do not correct their words when they hear the error immediately. Arabic teachers are not accompanied by good accompaniment to students when speaking and others.